Peran Prokrastinasi Akademik terhadap Ketidakjujuran Akademik pada Mahasiswa: Systematic Literature Review - Vivin Ainun Nuha; Nida Hasanati (Education Achievement: Journal of Science and Research, 2025)
This study aims to examine the role of academic procrastination in influencing academic dishonesty among college students using a systematic literature review (SLR) approach. A total of 16 articles published across several academic databases were analyzed by considering thematic relevance, methodological rigor, and empirical findings. The results indicate that most studies report a positive and significant relationship between procrastination and academic dishonesty. Students who tend to delay their academic demands, making them more vulnerable to dishonest behaviors such as plagiarism and cheating. Several studies also identify additional factors that strengthen the relationship between the two variables, including academic pressure, low self-efficacy, peer conformity, and poor time management. Although some research reports a non-significant relationship, these variations are influenced by differences in sample characteristics and learning contexts. Overall, the findings affirm that academic procrastination plays a substantial role in promoting academic dishonesty. The implications highlight the importance of institutional interventions that enhance self-regulation. Time management skills, and academic integrity to reduce dishonest behaviors among students.